Constituents of Political Theory : Selected Articles of the Warsaw School of Political Theory - Sulowski, Stanislaw; Pierzchalski, Filip; Tobiasz, Marcin; Karwat, Mirosław (2021)
The book presents a collection of articles authored by several members of the Warsaw School of Political Theory, affiliated with the University of Warsaw. The team of scholars, whose roots extend to the 1970s when professor Artur Bodnar founded the Political Theory Research Group at University of Warsaw’s Methodical Centre for Political Science (COM SNP), has been conducting research under the leadership of professor Miros³aw Karwat. The school’s most distinguishing features include: the acceptance of the directives and principles of methodological holism, the acceptance and creative development of holistic integral definitions, the application of sociocentric spatial analyses, and a critical approach to the “cratocentric” tradition.